20th AIAA International Space Planes and Hypersonic Systems and Technologies Conference 2015
DOI: 10.2514/6.2015-3509
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Study of Optimized Hypersonic Leading Edge Geometries

Abstract: An aerothermal optimization study of two-dimensional hypersonic leading edge geometries has been performed. The accuracy of a simplified model and a reduced order numerical model was assessed through comparison to simulations of the compressible Navier-Stokes equations performed in OpenFOAM. Specifically, the estimated surface pressure, and laminar convective heating distributions have been compared. The simplified model was found to have compromised accuracy in regions of high and low surface curvature. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Convective heat-flux databases for the un-swept leading edge region of the vehicles (where the heat flux is expected to be the highest) are generated using the Newton-Kays model presented in [16] and adopted in [17] for a rapid shape optimisation study.…”
Section: B Aerothermodynamicsmentioning
confidence: 99%
“…Convective heat-flux databases for the un-swept leading edge region of the vehicles (where the heat flux is expected to be the highest) are generated using the Newton-Kays model presented in [16] and adopted in [17] for a rapid shape optimisation study.…”
Section: B Aerothermodynamicsmentioning
confidence: 99%
“…In a supersonic flow, the residence time of the flow is very short, but the aerodynamic load is high, so it is not possible to control the flow through mechanically moving components, as in a subsonic region. At the early age of cutting-edge design optimization studies [1][2][3], fixed structures like aero spikes [4][5][6][7] were suggested. However, the structure has other problems, like excessive thermal loads at the tip, additional loads at off-design operations, and induced moment during the maneuvering flight.…”
Section: Introductionmentioning
confidence: 99%